2008
DOI: 10.4067/s0717-97072008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Computational Study of Copper (Ii) Alkylpyrazolone Based Enamine Complex

Abstract: The cyclic voltammograms (CV) of the copper complex CuL 2 , L: C 19 H 26 N 3 O [1-(n-hexyl)-3-methyl-4-[1-phenylaminopropylidene]-2-pyrazolin-5-one] have been studied. The CV profiles of CuL 2 show one or two reduction and oxidation wave. The energy level corresponding to the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of CuL 2 have been determined experimentally from the first oxidation and reduction onset potential, respectively. These values were also estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…5,6 The polymeric precursors employed have been a series of heterocyclic α, β'-unsaturated ketones containing thiophene rings 4,5,7,8 similar to the molecule reported in this work and it has been studied and characterized by electrochemical and ab-initio methods. 9,10 Computational studies proved that the conformation of these molecules are the result of the interaction between the electronic pair of the oxygen in the carbonyl group and the heteroatom in the neighboring ring, indicating a favored conformation. [11][12][13] Electrochemical studies showed the existence of irreversible and asymmetrical peaks.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The polymeric precursors employed have been a series of heterocyclic α, β'-unsaturated ketones containing thiophene rings 4,5,7,8 similar to the molecule reported in this work and it has been studied and characterized by electrochemical and ab-initio methods. 9,10 Computational studies proved that the conformation of these molecules are the result of the interaction between the electronic pair of the oxygen in the carbonyl group and the heteroatom in the neighboring ring, indicating a favored conformation. [11][12][13] Electrochemical studies showed the existence of irreversible and asymmetrical peaks.…”
Section: Introductionmentioning
confidence: 99%